Analisis Peluang dan Potensi Akad Musyarakah dalam Meningkatkan Akses Pembiayaan UMKM pada BTN Syariah - Royyan Ramdani Djayusman; Rafi Nur Azizah (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study analyzes the opportunities and potential of musyarakah contracts in increasing access to financing for Micro, Small and Medium Enterprises (MSMEs) at BTN Syariah. The musyarakah contract is a form of sharia-based financing that emphasizes the principle of profit sharing between banks and customers. However, the application of this contract still faces various challenges, such as the risk of moral hazard, lack of This research uses a descriptive qualitative method with a case study approach at BTN Syariah. Data were collected through interviews with bank parties, document analysis, and literature review related to the policy and implementation of musyarakah contracts in Islamic banking. The results show that musyarakah contracts have great potential in increasing access to financing for MSMEs because they are flexible and oriented towards business partnerships. In addition, the profit-sharing mechanism allows MSMEs to obtain capital without the burden of fixed interest, which is often an obstacle in conventional financing schemes. However, for the musyarakah contract to be optimized, a comprehensive strategy is needed, such as strengthening risk mitigation, increasing financial literacy for MSME players, and more accommodating regulatory support. BTN Syariah also needs to develop musyarakah-based product innovations that are more adaptive to the needs of MSMEs. By optimizing the musyarakah contract, it is hoped that access to MSME financing will be wider, so as to encourage inclusive and sustainable economic growth.